Ekonomi Berkelanjutan Melalui Budidaya Lele di Kelurahan Cipondoh - Kurniawan, Zaqi; Tiaharyadini , Rizka; Anif , Muhammad (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2024)
This community service activity aims to enhance community assets to support sustainable mobility through the utilization of green spaces and economically valuable catfish farming in Cipondoh Village, Tangerang City. The method used involves a participatory approach, where residents actively participate in the planning, implementation, and evaluation of activities. Students contribute by assisting residents and ensuring the effective transfer of knowledge and skills. The results of the activities show a significant increase in residents' knowledge and awareness regarding the importance of green spaces and catfish farming. Active participation reached 95%, demonstrating high enthusiasm and program effectiveness. This success not only improves the local environment and economy but also shows great potential for implementation in other areas. This program supports sustainable development goals by creating a more environmentally conscious and economically empowered community.sustainable mobility, green spaces, catfish farming, community empowerment, local economy